Analisis Kemampuan Berpikir Kreatif Peserta Didik SMP dalam Menyelesaikan Permasalahan Aljabar di Era Pandemi - Vindry Rika Yunika; Ishaq Nuriadin (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
The purpose of this research is to analyze the mathematical creativity skills of junior high school students in solving algebra cases during the pandemic. The research method used is descriptive qualitative. The subjects of this study were 33 students in class VII B at 253 State Junior High School in Jakarta. The research technique used a descriptive mathematical creative thinking test instrument on algebraic material and carried out interviews with 3 screened students who were randomly selected according to their level of creative thinking. In this study, there are four indicators of mathematical creative thinking, namely fluency, flexibility, originality, and elaboration. The results of this study revealed 14 students who have low mathematical creative thinking skills, 11 students who have moderate mathematical creative thinking abilities, and 8 students who have high mathematical creative thinking abilities